Highly oxygenated sterols from the starfish Archaster typicus - Minh, Chau Van; Cuong, Nguyen Xuan; Thanh, Nguyen Van; Huong, Hoang Thanh; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
Three highly oxygenated sterols named ergost-22-ene-3β,4β,5α,6α,8β,14α,15α,25R,26-nonol, 27-norcholestane-3β,4β,5α,6α,7β,8β,14α,15α,24R-nonol, 27-norcholestane-3β,4β,5α,6α,8β,14α, 15α,24R-octol were isolated from the methanolic extract of the starfish Archaster typicus. Their structures were determined by the physicochemical and spectral data in comparison with the reported literature. This is the first report of these compounds from the Vietnamese starfish Archaster typicus